Overexpression of Homer1a in the basal and lateral amygdala impairs fear conditioning and induces an autism-like social impairment. Issue 1 (December 2016) - Banerjee, Anwesha; Luong, Jonathan; Ho, Anthony; Saib, Aeshah; Ploski, Jonathan
Abstract Background Autism spectrum disorders (ASDs) represent a heterogeneous group of disorders with a wide range of behavioral impairments including social and communication deficits. Apart from these core symptoms, a significant number of ASD individuals display higher levels of anxiety, and some studies indicate that a subset of ASD individuals have a reduced ability to be fear conditioned. Deciphering the molecular basis of ASD has been considerably challenging and it currently remains poorly understood. In this study we examined the molecular basis of autism-like impairments in an environmentally induced animal model of ASD, where pregnant rats are exposed to the known teratogen, valproic acid (VPA), on day 12.5 of gestation and the subsequent progeny exhibit ASD-like symptoms. We focused our analysis on the basal and lateral nucleus of the amygdala (BLA), a region of the brain found to be associated with ASD pathology. Methods We performed whole genome gene expression analysis on the BLA using DNA microarrays to examine differences in gene expression within the amygdala of VPA-exposed animals. We validated one VPA-dysregulated candidate gene (Homer1a ) using both quantitative PCR (qRT-PCR) and western blot. Finally, we overexpressed Homer1a within the basal and lateral amygdala of naïve animals utilizing adeno-associated viruses (AAV) and subsequently examined these animals in a battery of behavioral tests associated with ASD, including auditory fear conditioning, social interaction and open field. Results Our microarray data indicated thatHomer1a was one of the genes which exhibited a significant upregulation within the amygdala. We observed an increase inHomer1a messenger RNA (mRNA) and protein in multiple cohorts of VPA-exposed animals indicating that dysregulation of Homer1a levels might underlie some of the symptoms exhibited by VPA-exposed animals. To test this hypothesis, we overexpressed Homer1a within BLA neurons utilizing a viral-mediated approach and found that overexpression of Homer1a impaired auditory fear conditioning and reduced social interaction, while having no influence on open-field behavior. Conclusions This study indicates that dysregulation of amygdala Homer1a might contribute to some autism-like symptoms induced by VPA exposure. These findings are interesting in part because Homer1a influences the functioning of Shank3, metabotropic glutamate receptors (mGluR5), and Homer1, and these proteins have previously been associated with ASD, indicating that these differing models of ASD may have a similar molecular basis.